Contextualisation of Geometry Tasks in High School Mathematics Textbooks - Litoldo, Beatriz Fernanda; Amaral, Rúbia Barcelos [UNESP]; Mazzi, Lucas Carato [UNESP] (My University, 2022)
Background: Geometry is often seen as an area of mathematics that is present in everyone’s daily life. Looking around, we see it in the shapes of objects, in nature, etc. Therefore, it would be natural to expect that its approach in textbooks, for example, would bring different contexts in which it would be present. Objective: To discuss how contexts are introduced in geometry tasks in a collection of mathematics textbooks. Design: We use a qualitative approach of the documentary type as a methodology. Environment and participants: A collection of high school mathematics textbooks approved by the National Textbook and Didactic Material Program – 2018 was selected. Data collection and analysis: Data were produced, organised, and analysed using horizontal and vertical analysis methods in each collection volume, according to the different references of contexts. Results: They concern the different references of contexts involved in the tasks. From the 1,335 tasks analysed, 1,108 were contextualised in purely mathematical situations, while the rest, 227, were in contexts of reality. In this, there are 215 referring to reasonable semi-realities, and, on the other hand, the real context contemplates only three. Finally, nine concern tasks in unreasonable semi-real contexts. Conclusions: The restriction of the different context references that students can experience from this collection is discussed. The contexts presented do not include a broad spectrum based on a diversity of experiences among the different references of contexts.
Keywords: Contextualisation; Geometry; High school; Tasks; Textbooks